The Relationship Between Peer Attachment and Self-Regulation with Student Online Game Addiction at Sman 42 Jakarta - Christian Maranatha; Sondang Maria J Silaen (Journal of Social Research, 2023)
This study aims to determine the relationship between peer attachment and self–regulation with online game addiction. The sample of this study was a class X students of SMAN 42 Jakarta totaling 140 students. This study uses a double correlation test technique, the data collected is analyzed using the SPSS 24.0 for Windows computer program. The results showed a significant positive relationship between the attachment of peers and students at SMAN 42 Jakarta, with p = 0.000 and r = 0.327. The second results shows a significant negative relationship between self–regulation and student addiction of students at SMAN 42 Jakarta, with p = 0.000 and r = -0.483. The results of the multiple correlation test show a significant relationship between the attachment of peers and self – regulation with student addiction of students at SMAN 42 Jakarta, with SIG. F Change = 0.000, R = 0.580 value, and R Square value = 0.336. Based on the description above, it can be concluded that there is a relationship between the attachment of peers and self – regulation with student addiction of students at SMAN 42 Jakarta. The implications of this research are expected to be able to avoid associations to play online games and increase self – regulation by prioritizing school assignments.